PENGARUH VARIABEL INTERVENING KECUKUPAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP HUBUNGAN ANTARA PARTISIPASI PENGANGGARAN DAN KINERJA MANAJER DI INDONESIA - Supriyono, R.A. Supriyono (Journal of Indonesian Economy and Business, 2004)
This study explores the linkages budget participation and managers performance inIndonesia. In the theoretical model budget participation affects totally to managersperformance and this affects can directly or indirectly via two intervening variable: budgetadequacy and organizational commitment. To test the relationship, a survey questionnairewas administered to managers of going public corporation in Bursa Efek Jakarta (BEJ).Results of path analysis support the hypothesized relationships.Keywords: budget participation, manager performance, budget adequacy, organizationalcommitment